2020
DOI: 10.1101/2020.11.25.397380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-based integration of citizen-science data from disparate sources increases the precision of bird population trends

Abstract: AimTimely and accurate information on population trends is a prerequisite for effective biodiversity conservation. Structured biodiversity monitoring programs have been shown to track population trends reliably, but require large financial and time investment. The data assembled in a large and growing number of online databases are less structured and suffer from bias, but the number of observations is much higher compared to structured monitoring programs. Model-based integration of data from these disparate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Still, the greater magnitude of interspecific over intraspecific variation supports the use of mean trait values in trait‐based ecology, at least for species–environment relationships. Ultimately, growing citizen science data will likely form a major component of future understanding of species–environment relationships for both basic (Soroye et al, 2018) and applied (Hertzog et al, 2021) research. Since species differences may drive evolutionary and ecological change within biological communities (Trevail et al, 2021), citizen science data offers an excellent opportunity to further our understanding of variability in species–environment relationships and how it impacts species' responses to anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the greater magnitude of interspecific over intraspecific variation supports the use of mean trait values in trait‐based ecology, at least for species–environment relationships. Ultimately, growing citizen science data will likely form a major component of future understanding of species–environment relationships for both basic (Soroye et al, 2018) and applied (Hertzog et al, 2021) research. Since species differences may drive evolutionary and ecological change within biological communities (Trevail et al, 2021), citizen science data offers an excellent opportunity to further our understanding of variability in species–environment relationships and how it impacts species' responses to anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…However, simulation‐based studies have shown that poor estimates can be obtained when biases in presence‐only data are unknown and hence not accounted for (Ahmad Suhaimi et al, 2021; Simmonds et al, 2020). When estimating population trends, data integration of large CS list data and structured data can reduce bias (Boersch‐Supan & Robinson, 2021; Hertzog et al, 2021; Pagel et al, 2014).…”
Section: Statistical Modelsmentioning
confidence: 99%
“…Although both are valuable for addressing a wide range of socio‐ecological research questions and biological modelling and monitoring approaches (Chandler et al, 2017; Neate‐Clegg et al, 2020), doubts still exist about data quality from citizen science surveys (Aubry et al, 2017; Jiménez et al, 2019). The data combination from different sources also proved to be a useful tool in ecological modelling (Miller et al, 2019; Suhaimi et al, 2021), specifically to improve estimates of species distributions (Isaac et al, 2020; Robinson et al, 2020), abundance and population trends (Boersch‐Supan et al, 2019; Hertzog et al, 2021). However, there is still much to explore on the data quality (Johnston et al, 2019; Van Eupen et al, 2021) and usefulness of each input data source through the modelling process (Kobori et al, 2016; Kosmala et al, 2016), as well as the uncertainty hosted in each modelling step should also be controlled more exhaustively.…”
Section: Introductionmentioning
confidence: 99%